Comprehensive Roles and Future Perspectives of Exosomes in Peritoneal Metastasis of Gastric Cancer - Chen, Xiangliu; Wang, Haiyong; Huang, Yingying; Chen, Yanyan; Chen, Chuanzhi; Zhuo, Wei; Teng, Lisong (Frontiers in Oncology, 2021)
Gastric cancer (GC) is one of the most prevalent digestive malignancies. A great number of patients at first visit or post curative resections are diagnosed with widespread metastasis within the peritoneal cavity. Overwhelming evidence has demonstrated that exosomes, a variety of biologically functional extracellular vesicles comprising active factors, mediate the progression and metastasis of GC. Although the regulatory mechanisms of exosomes remain fairly elusive, they are responsible for intercellular communication between tumor cells and normal stroma, cancer-related fibroblasts, immune cells within the primary tumor and metastatic niche. In this review, we provide new insight into the molecular signatures of GC-associated exosomes in reprogramming the tumor microenvironment and the subsequent promotion of peritoneal metastasis—including infiltration of the gastric wall, implantation of tumor cells onto the pre-metastatic peritoneum, and remodeling of the pre-metastatic niche. Based on this review, we hope to draw a more general conclusion for the functions of exosomes in the progression and peritoneal metastasis of GC and highlight the future perspective on strategies targeting exosomes in prognostic biomarkers and therapy for peritoneal metastasis.